Diagnostic and therapeutic medical devices for safer blood management in cardiac surgery: systematic reviews, observational studies and randomised controlled trials - Gavin J Murphy; Andrew D Mumford; Chris A Rogers; Sarah Wordsworth; Elizabeth A Stokes; Veerle Verheyden; Tracy Kumar; Jessica Harris; Gemma Clayton; Lucy Ellis; Zoe Plummer; William Dott; et al. (Programme Grants for Applied Research, 2017)
Background: Anaemia, coagulopathic bleeding and transfusion are strongly associated with organ failure, sepsis and death following cardiac surgery. Objective: To evaluate the clinical effectiveness and cost-effectiveness of medical devices used as diagnostic and therapeutic tools for the management of anaemia and bleeding in cardiac surgery. Methods and results: Workstream 1 – in the COagulation and Platelet laboratory Testing in Cardiac surgery (COPTIC) study we demonstrated that risk assessment using baseline clinical factors predicted bleeding with a high degree of accuracy. The results from point-of-care (POC) platelet aggregometry or viscoelastometry tests or an expanded range of laboratory reference tests for coagulopathy did not improve predictive accuracy beyond that achieved with the clinical risk score alone. The routine use of POC tests was not cost-effective. A systematic review concluded that POC-based algorithms are not clinically effective. We developed two new clinical risk prediction scores for transfusion and bleeding that are available as e-calculators. Workstream 2 – in the PAtient-SPecific Oxygen monitoring to Reduce blood Transfusion during heart surgery (PASPORT) trial and a systematic review we demonstrated that personalised near-infrared spectroscopy-based algorithms for the optimisation of tissue oxygenation, or as indicators for red cell transfusion, were neither clinically effective nor cost-effective. Workstream 3 – in the REDWASH trial we failed to demonstrate a reduction in inflammation or organ injury in recipients of mechanically washed red cells compared with standard (unwashed) red cells. Limitations: Existing studies evaluating the predictive accuracy or effectiveness of POC tests of coagulopathy or near-infrared spectroscopy were at high risk of bias. Interventions that alter red cell transfusion exposure, a common surrogate outcome in most trials, were not found to be clinically effective. Conclusions: A systematic assessment of devices in clinical use as blood management adjuncts in cardiac surgery did not demonstrate clinical effectiveness or cost-effectiveness. The contribution of anaemia and coagulopathy to adverse clinical outcomes following cardiac surgery remains poorly understood. Further research to define the pathogenesis of these conditions may lead to more accurate diagnoses, more effective treatments and potentially improved clinical outcomes. Study registration: Current Controlled Trials ISRCTN20778544 (COPTIC study) and PROSPERO CRD42016033831 (systematic review) (workstream 1); Current Controlled Trials ISRCTN23557269 (PASPORT trial) and PROSPERO CRD4201502769 (systematic review) (workstream 2); and Current Controlled Trials ISRCTN27076315 (REDWASH trial) (workstream 3). Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 5, No. 17. See the NIHR Journals Library website for further project information.